Disiplin Kerja Terhadap Kompetensi Profesional Guru Di Sma Se-Kecamatan Nanggung Bogor - Fitriani, Neng Siska Fitriani; Rahmawati, Ima; Lestari, Hana; Trimulyo, Joko (JURNAL KAJIAN ISLAM MODERN, 2024)
This study was conducted to test the hypothesis whether there is an influence between work discipline on the professional competence of teachers at SMA Se-Kecamatan Nanggung Bogor. This research uses quantitative with survey method. The sample amounted to 24 teachers. The data used are secondary data and primary data obtained from questionnaires and processed using simple regression statistics. Based on the regression test obtained Sig. value of 0.003 <0.01, it can be concluded that there is a positive and significant influence between work discipline on teacher professional competence.